Butterflies, Orchids and Wasps. Polyglossia and Aesthetic Lives: Foreign Languages in The Spirit Lamp (1892-1893) - Xavier Giudicelli (Cahiers Victoriens et Edouardiens)
This paper focuses on The Spirit Lamp, a short-lived undergraduate periodical whose fifteen issues were published in Oxford by the bookseller James Thornton between May 1892 and June 1893 and edited first by J. S. Phillimore and Sandys Wason, then by Lord Alfred Douglas (for the last six issues). One of the characteristics of this journal is that, beside several translations, it features quite a lot of material written in foreign languages. The presence of ancient languages, Greek in particular, is noteworthy. It corresponds to the already well-documented link between Hellenism and homosexuality. Yet the presence of modern languages, and of French in particular—albeit in my opinion one of the salient features of The Spirit Lamp—is usually overlooked. The aim of this paper is to show that the polyglossia of The Spirit Lamp is an essential part of an aestheticization of life and the expression of otherwise unspeakable desires. It equally involves performance: a homosexual identity is created through this performance, blurring the limit between art and life. I also argue that what we witness in The Spirit Lamp is the creation of a hybrid language based on the setting up of a framework of reference other than British and on the defamiliarization of the English language.